1979
DOI: 10.3758/bf03329407
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of fluid deprivation on the acquisition and extinction phases of a conditioned taste aversion

Abstract: Previous work has shown that the rate of extinction of a conditioned taste aversion by a male (but not a female) rat is affected by the state of fluid deprivation. In the present study. adult male rats were either fluid deprived or nondeprived during acquisition of the conditioned taste aversion and then either fluid deprived or nondeprived during its extinction. The males that were fluid deprived during extinction showed a faster. female-like rate of extinction regardless of the deprivation state during acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Although acquisition of CT A would occur under fluid-deprived conditions, the protocol allowed the extinction phase of the experiment to be conducted under nondeprived conditions. Sengstake and Chambers (1979) had observed that a similar paradigm was as effective in producing the sexual dimorphism in extinction rate as was a paradigm in which both acquisition and extinction were conducted under nondeprived conditions. tion, there was a significant Sex by Day interaction [F(4,IOO)=3.74, p < .01].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although acquisition of CT A would occur under fluid-deprived conditions, the protocol allowed the extinction phase of the experiment to be conducted under nondeprived conditions. Sengstake and Chambers (1979) had observed that a similar paradigm was as effective in producing the sexual dimorphism in extinction rate as was a paradigm in which both acquisition and extinction were conducted under nondeprived conditions. tion, there was a significant Sex by Day interaction [F(4,IOO)=3.74, p < .01].…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was designed to follow the protocol of previous studies which induced CTA under nondeprived conditions (Chambers, 1976;Chambers & Sengstake, 1976, 1978Sengstake & Chambers, 1979). A comparison of resistance to extinction was made between two genotypes of mice of both sexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both of these assessments, there was no difference in the overall pattern of responding between the deprivation conditions with adolescent animals displaying attenuated aversions in comparison to the adults (Hurwitz et al, 2012). Further, the age difference in the aversive effects of MDMA was still evident in the two-bottle test, an assessment that is less influenced by fluid deprivation given that it does not require animals to consume saccharin when the water choice is freely available (Grote & Brown, 1971;Sengstake and Chambers, 1979). Although motivation to drink may not have been a contributing factor, it is nonetheless possible that the fluid deprivation schedule employed was more stressful in the adolescent subjects relative to their adult counterparts.…”
Section: Developmental Psychobiologymentioning
confidence: 98%
“…For instance, sex differences in conditioning acquisition have been observed in fear conditioning (see above) or eye-blink conditioning (apparently being stronger in females; for instance see Waddell et al, 2008) but not in other models such as conditioned taste aversion (CTA; for instance see Randall-Thompson and Riley, 2003;Angulo and Arévalo-Romero, in press;Jones et al, 2006;Pittman et al, 2008;Rinker et al, 2008). Finally, within the same experimental model, specifically CTA, sex differences might be observed in some effects as extinction (e.g., Chambers and Sengstake, 1979;Sengstake and Chambers, 1979) or latent inhibition (e.g., Nofrey et al, 2008;Quinlan et al, 2010) but not in others as acquisition (e.g., Randall-Thompson and Riley, 2003;Jones et al, 2006;Pittman et al, 2008;Rinker et al, 2008). According to the evidence, thus, it seems reasonable to assume that the hypothesis of a general sex difference for certain conditioning effects will require a confirmation from studies using different experimental preparations.…”
Section: Introductionmentioning
confidence: 97%